Stereoretentive Olefin Metathesis: A New Avenue for the Synthesis of All-cis Poly(p-phenylene vinylene)s and Stereodefined Polyalkenamers - Kempel, Samuel J.; Hsu, Ting-Wei; Michaudel, Quentin (Synlett, 2021)
Olefin metathesis has tremendously impacted all fields of synthetic chemistry. However, the control of the olefin stereochemistry during this process remains a grand challenge. Recent innovations in catalyst design have permitted control of the stereochemistry of the olefin product. Here, we discuss the development of stereoretentive olefin metathesis, with an emphasis on the synthesis of stereodefined polyalkenamers through ring-opening metathesis polymerization (ROMP). We then present our application of this unique reaction manifold to the preparation of all-cis poly(p-phenylene vinylene)s (PPVs). A dithiolate Ru catalyst was found to deliver perfect cis selectivity for the polymerization of a paracyclophane diene monomer. By using optimized conditions, all-cis PPVs with narrow dispersities and predictable molar masses were obtained by varying the ratio of monomer to catalyst. The high chain fidelity of the stereoretentive ROMP with a paracyclophane diene monomer enabled the preparation of well-defined diblock copolymers with a norbornene co-monomer. Photochemical isomerization of all-cis to all-trans PPVs was effected with both homopolymers and diblock copolymers. This process was shown to be selective for the PPV block, and resulted in changes in optical properties, polymer size, and solubility. Stereoretentive ROMP provides a promising platform for synthesizing polymers with unique properties, including photoresponsive all-cis PPVs with living characteristics.1 Introduction2 Synthetic Applications of Stereoretentive Olefin Metathesis3 Stereocontrol of Polyalkenamers through Stereoretentive ROMP4 Stereoretentive ROMP To Access All-cis Poly(p-phenylene vinylene)s5 Conclusion
Keywords: stereoretentive polymerizationolefin metathesis; ring-opening metathesis polymerization; polyphenylene vinylenes; polyalkenamers; photoresponsive materials